2022
DOI: 10.1139/cjz-2021-0210
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of cold snaps and agriculture on the growth rates of Tree Swallows (Tachycineta bicolor)

Abstract: The decline of avian aerial insectivores has been greater than any other foraging guild and both climate change and agricultural intensification are leading hypotheses explaining this decline. Spring cold snaps are predicted to increase in frequency due to climate change, and factors associated with agricultural intensification (e.g., toxicological agents, simplification of agricultural landscapes, and reductions of insect prey) potentially exacerbates the negative effects of cold snaps on aerial insectivore n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…In fact, evidence suggests food provisioning Tree Swallows as well as their broods already incur these types of costs. For example, parents breeding in more agro-intensive landscapes spend less time in the nest (Garrett et al, 2022b;Stanton et al, 2016), express reduced body condition (Pigeon et al, 2013;Stanton et al, 2017), and both reduced fledging success and nestling growth (Garrett et al, 2022a;Houle et al, 2020). Some of these natal effects are of concern as they may be carried over into later life stages (Harrison et al, 2011).…”
Section: Durationmentioning
confidence: 99%
“…In fact, evidence suggests food provisioning Tree Swallows as well as their broods already incur these types of costs. For example, parents breeding in more agro-intensive landscapes spend less time in the nest (Garrett et al, 2022b;Stanton et al, 2016), express reduced body condition (Pigeon et al, 2013;Stanton et al, 2017), and both reduced fledging success and nestling growth (Garrett et al, 2022a;Houle et al, 2020). Some of these natal effects are of concern as they may be carried over into later life stages (Harrison et al, 2011).…”
Section: Durationmentioning
confidence: 99%
“…Their research adds to growing evidence that wetland loss reduces the abundance of valuable aquatic insect prey during the breeding season with apparent individual and demographic consequences (Elgin et al 2020;Berzins et al 2021;Génier et al 2021). The contribution by Garrett et al (2022) provides strong evidence that the interacting effects of cold snaps and agricultural intensity in the form of mono-cropping have negative effects on multiple measures of Tree Swallow chick growth relative to landscapes with less intensive agriculture (e.g., forage crops, pastures). The results of this study complement other research that showed that extreme weather events have detrimental effects on Tree Swallow offspring but with the added landscape component (Cox et al 2020;Shipley et al 2020).…”
mentioning
confidence: 92%